BEREL'DEKİ 11. KURGAN VE PAZIRIK KÜLTÜRÜ / KURGAN 11 at BEREL and PAZYRYK CULTURE - KUTLU, MEHMET; Kutlu, Leila (Sanat Tarihi Dergisi, 2020)
Berel Kurgans are located in the western end of the Altai Mountains, the Eastern Kazakhstan Province of Republic of Kazakhstan. There are more than 100 kurgans identified. Kurgan 11 is one of the biggest kurgans at Berel burial ground. The kurgan is considered to belong to a royal dynasty member both for architectural features and rich artifacts. Kurgan 11 at Berel, which is the branch of the Pazyryk Culture in Eastern Kazakhstan, was excavated by Professor Zainolla Samashev and his team in 1998. According to dendrochronological analysis it is dated to 4th century BC. This study is based on the authors’ participation in the archaeological excavations conducted at Berel in the summer of 2019 and their on-site observations as well as on review of the scientific literature. Particularly, we evaluated the results of the assessments and analyzes of well-preserved findings and some organic materials through the permafrost conditions obtained from Kurgan 11 at Berel. Firstly, the architecture of the kurgan and its structural features that provide the necessary conditions for the formation of permafrost layers are examined. Then, the data concerning the people buried in the kurgan, their belongings and horse burials that were put to accompany them in their eternal life were also reviewed. Finally, the assessment of the artifacts and findings of the Kurgan 11 exhibited in the Berel Museum was conducted based on the onsite observations.